Folklorizing northern khmer identity in thailand: Intangible cultural heritage and the production of “good culture” - Denes A. (Institute of Southeast Asian Studies, 2015)
© 2015 ISEAS. Growing recognition of the contested nature of heritage has prompted critical reassessments of official heritage discourses and the demand for more inclusive heritage processes. Field research in Surin, Thailand, reveals the challenges of implementing participatory approaches in a context in which the concept of cultural heritage is employed to domesticate the nation’s ethnic Others. The history of state-sponsored, folklorized performances of the ethnic Khmer genre of kantruem demonstrates the ways in which the recent listing of kantruem on Thailand’s national registry of “intangible culture” elides histories of cross-border linkage with Cambodia and meanings of kantruem as a site of memory and affect.